Resiliencia, optimismo, esperanza y sentido de vida en el adulto mayor con y sin enfermedad crónica de la ciudad de Bogotá (2021)
The appearance of chronic diseases impacts the quality of life, well-being and functioning of the elderly, thence the need to enhance the psychological qualities and resources that positively affect their quality of life. In this sense, the objective of the research was to describe the levels of resilience, optimism, hope and sense of life in the elderly with or without chronic disease. The study design is descriptive, correlational, cross-sectional by survey. For this, 200 people were selected, 100 who had a chronic disease and 100 who did not have it, selected through non-random sampling of available subjects residing in Bogotá. The analysis was performed based on the following instruments: Connor-Davidson Resilience Scale Questionnaire (CD-RISC 10), Dispositional Optimism Scale (DIOP), Adult Hope scale AHS and Vital Purpose Test (PIL). The results indicate that the older adult with chronic disease has lower levels of resilience, optimism, hope and sense of life, compared to the older adult without chronic disease.